CONSOLIDATION ZONES FEATURES FORMATION OF A GROUND AROUND SQUARE SHAPED PILES - Malyshev, O. V. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Necessity to resolve the problem of concerning the analytical dimensions definition and constructing forms of compacted zones of ground around the lateral surface of square cross section pile in normal to pile axis direction are shown in this article. Various analytical methods of ground compacted zones radius determination around cylindrical elements driven into the ground considering its initial state were analyzed. Graph-analytical method of ground compaction zones construction around square cross-section piles was developed. Efficiency of the developed methodology and analytical expressions using possibility to determine the radius of compaction zone of a ground around the driven or jacked-in elements is confirmed by comparing obtained solutions with the experimental data. The developed methodology allows increasing the efficiency and reliability of piles and pile foundations use due to their rational design.